Why Sexual Privacy Matters for Trust - Danielle Keats Citron (Washington University Law Review, 2019)
Every generation has preferred modes of self-disclosure. Not long ago, lovers revealed their thoughts, desires, and secrets over the phone and in letters. Today, they exchange personal histories and nude photos via text and online chats. Yet no matter the era’s chosen mode of communication, the success of intimate relationships depends upon sexual privacy. Intimacy can develop only if partners trust each other to treat their self-revelations with discretion and care. Self-disclosure, however, is difficult after one’s nude photos have been posted online or one’s intimate encounters have been videotaped without permission. Individuals refrain from dating for fear that their intimate revelations will again be surveilled and exposed in unwanted ways. Sexual-privacy invasions thus undermine the possibility of intimate relationships. Law should punish intimacy-destroying invasions of sexual privacy, and market efforts should be trained on their prevention and mitigation. Some private responses, however, require a healthy dose of skepticism as they over-promise and under-deliver for sexual privacy.
Keywords: Sexual privacy; Privacy law; Intimate relationships; Sexual-privacy invasions; Sexual agency